An Exploration of Culture in Listening and Speaking Materials from an English as an International Language Perspective - Rattanawong, Amonrat; Thongrin, Saneh (LEARN Journal: Language Education and Acquisition Research Network, 2023)
As material that projects linguistic and cultural knowledge to students, English Language learning textbooks shape students’ learning in various educational contexts. However, many textbooks have been found to perpetuate Anglo-Western norms and beliefs; thus, they fail to represent local students’ socio-cultural backgrounds. With this in mind, our study analyzes listening–speaking sections of ten textbooks used in leading Thai universities. More specifically, through a perspective on cultural content sources (i.e., local, target, international, and neutral content), in combination with a deeper two-level analysis of such cultural content (surface and deep), we explore cultural contents integrated in listening-speaking sections of the ten textbooks selected. Findings indicated that three patterns of multiple cultural contents were well integrated in five of the ten textbooks: Touchstone, Speakout, Navigate, Unlock, and Prism. These five books seemed to embrace much broader multicultural content that represented non-Western students’ histories and their global counterparts. Despite the overall low frequency of local students’ realities portrayed in the sampled textbooks, our findings indicate that textbook authors and publishers have begun to acknowledge students’ realities in terms of English being an international language. We suggest directions practitioners and researchers can explore so that learners can be exposed to linguistically and culturally appropriate content.